2000
DOI: 10.1128/iai.68.8.4523-4530.2000
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Epithelial Cells byYersinia pestis: Evidence for aY. pestis-Specific Invasin

Abstract: The causative agent of plague, Yersinia pestis, is regarded as being noninvasive for epithelial cells and lacks the major adhesins and invasins of its enteropathogenic relatives Yersinia enterocolitica and Yersinia pseudotuberculosis. However, there are studies indicating that Y. pestis invades and causes systemic infection from ingestive and aerogenic routes of infection. Accordingly, we developed a gentamicin protection assay and reexamined invasiveness of Y. pestis for HeLa cells. By optimizing this assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
122
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 55 publications
5
122
1
3
Order By: Relevance
“…A 9.5-kb plasmid (pPst/pPCP1) encodes the plasminogen activator Pla (ref. 8), a putative invasin that is essential for virulence by the subcutaneous route. A 100±110-kb plasmid (pFra/pMT1) encodes murine toxin Ymt and the F1 capsular protein, which have been shown to have a role in the transmission of plague.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A 9.5-kb plasmid (pPst/pPCP1) encodes the plasminogen activator Pla (ref. 8), a putative invasin that is essential for virulence by the subcutaneous route. A 100±110-kb plasmid (pFra/pMT1) encodes murine toxin Ymt and the F1 capsular protein, which have been shown to have a role in the transmission of plague.…”
mentioning
confidence: 99%
“…Rough mutants of Y. enterocolitica show an enhanced ability to invade cultured cells, a suggested consequence of the enhanced accessibility of surface Ail 28 . However, a recent mutagenesis study in Y. pseudotuberculosis found that O-antigen mutants were unable to invade epithelial cells 29 and were attenuated when infecting mice both orally and systemically, suggesting that as Y. pestis is invasive 8 and virulent, it may have alternative surface structures that complement the loss of the O antigen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In airborne disease, penetration of epithelial cells may promote development of pulmonary lesions . Although Pla protease enhances interaction with epithelial cells (Cowan et al, 2000;Lahteenmaki et al, 1998Lahteenmaki et al, , 2001a, Psa fimbria have also been implicated. Neither is sufficient to confer complete internalization.…”
Section: Introductionmentioning
confidence: 99%
“…pestis enters epithelial cells, another mechanism to circumvent the immune response (Cowan et al, 2000). In airborne disease, penetration of epithelial cells may promote development of pulmonary lesions .…”
Section: Introductionmentioning
confidence: 99%